Application of 93Nb NMR spectroscopy to (silox)3Nb(Xn/Lm) complexes (silox = tBu3SiO): Where does (silox)3Nb(NN)Nb(silox)3 appear?. (8th January 2016) - Hulley, Elliott B.; Williams, Valerie A.; Hirsekorn, Kurt F.; Wolczanski, Peter T.; Lancaster, Kyle M.; Lobkovsky, Emil B.
Graphical abstract: 93 Nb NMR chemical shifts of (silox)3 Nb(Xn /Lm ) species follow the general trend of δ ∝ 1/ X ( X is Pauling electronegativity) and correlate with the paramagnetic term, which is governed by the second-order Zeeman effect, and estimated using the Average Excitation Energy (AEE) model. Abstract: 93 Nb NMR chemical shifts and linewidths are reported for the following 4-coordinate series of (silox)3 Nb(Xn /Lm ) species: Xn /Lm = NNCH(SiMe3 ), 1 NNT; O, 1O; Cl2, 2 –Cl2 ; 13 C 13 CO, 1 13 C 13 CO; CHCH3, 1 CHMe; CH2, 1 CH2 ; CH( trans -CHCHCH3 ), 1 –t-C4 H6 ; CH( trans -CHCH(CH2 )2 Ph), 1 –t-C5 H6 Ph; CH( cis -CHCHCH3 ), 1 –c-C4 H6 ; CH( cis -CHCH(CH2 )2 Ph), 1 –c-C5 H6 Ph; (η-C2 H4 ), 3 –C2 H4 ; (κ 2 -C, C–CH2 CHCHCH2 ), 2 –C4 H6 ; (η 2 -CD2 CH( trans -2-Ph- c Pr)), 3 –VyPh c Pr; P − [Li(THF) x ] +, 1 –PLi; PH, 1 PH; PMe, 1 PMe; [(silox)3 Nb]2 (μ:η 1, η 1 -N2 ), 1 2 –N2 . Small scale syntheses of1 NNT and2 –C4 H6 are given, and the preparation of1 2 –N2, is reported, along with its X-ray crystal structure, and electronic structure. Calculated (DFT) 93 Nb NMR chemical shifts correlate with the experimental values, and δ is found to be generally proportional to 1/ X ( X is Pauling electronegativity). This trend is derived from the paramagnetic contribution, which is governed by the second-order Zeeman effect, and estimated using the Average Excitation Energy (AEE) model.